Exploring Research Trends in Ecotourism in Indonesia: A Bibliometric Analysis - Salouw, Elvis; Pakniany, Yamres; Nugroho, Truli; Adinugroho, Suryo; Situmorang, Dokman Marulitua; Dahoklory, Junengsi Carli (Khizanah al-Hikmah : Jurnal Ilmu Perpustakaan, Informasi, dan Kearsipan, 2024)
This study aims to examine the evolution of research, identify trends, and visualize the landscape of ecotourism research in Indonesia using bibliometric methods. A total of 472 articles were retrieved from the Scopus database accessed on February 11, 2023. These articles were analyzed using VOSviewer and Microsoft Excel to map research trends and identify influential articles. The analysis reveals a significant increase in research on ecotourism in Indonesia over the past decade. Notably, several influential articles, including those featuring popular case studies within the Indonesian ecotourism context, were successfully identified. This study addresses a gap in the literature by providing insights into the trends and research opportunities in ecotourism in Indonesia. The findings are expected to be valuable for stakeholders, researchers, and practitioners in the tourism sector, particularly those involved in ecotourism development.